Combining traditional embryology lectures with technology and perception of students toward it - Priti Chaudhary; Kamal Arora; Shashi Kant Dhir (Wolters Kluwer Medknow Publications, 2018)
Background: Technology-enhanced learning is reliable, established, and effective teaching tool for better understanding of the subject. This study addresses an important issue in medical education, namely, the enhancement of the widely criticized lecture style of teaching by engaging students more actively during class through the use of videos or animations. This study describes the development, implementation, and evaluation of a traditional anatomy lecture series combined with technology. Aim and Objectives: The aim of the study is (a) to combine three-dimensional (3D) videos and animations with traditional embryology lectures and (b) to evaluate the 1st-year MBBS students' perception about this method of learning of embryology. Methodology: This qualitative study was conducted in the Department of Anatomy at Guru Gobind Singh Medical College, Faridkot, during the theory classes of embryology over a period of approximately 3 months among 100 1st-year MBBS students. The students were shown 3D videos and animations of embryology during traditional didactic lecture to explain all the aspects of the development of different systems of the body in 25 classes, of 1-h duration each. Feedback was taken using a structured questionnaire to know the perception of students toward this exercise of using technology during lecture of embryology. Results: A total of 100 MBBS first professional students took part in the study and submitted questionnaire. The students were satisfied with this method of technology-enhanced learning and described better understanding of the concepts with improved learning. More than 90% of the students found that combining 3D videos and animations with traditional lecture helped in solving the confusion and misconceptions regarding topic and did make the topic more interesting. They further added that they wanted to have such type of technology (videos)-enhanced lectures in all other topics of anatomy and in other subjects as well. Conclusions: Technology used in the form of 3D videos and animations changed their attitude toward learning and their learning was improved. It provided satisfaction to students in terms of better learning and understanding of the subject.